Comparative evidence for the importance of the amygdala in regulating reward salience. (August 2018) - Pryce, Christopher R
Highlights: Amygdala responds to stimuli of positive (reward) and negative (aversive) valence. Reduced reward salience is a major and trans-diagnostic psychopathology. Stress-induced amygdala changes could mediate reduced reward salience. Amygdala reward neurons constitute a potential target for restoring reward salience. Abstract : Environmental stimuli and life events are often of emotional relevance to the individual. This is due to their recognition and processing by the brain's neural circuits for emotion. In terms of emotion valence, stimuli/events can be neutral (non-emotional), rewarding or aversive. In addition to its basic valence, the salience of an emotional stimulus, that is, how rewarding or how aversive it is, is also of critical importance. Quantitative changes in stimulus reward salience or aversion salience are likely to underlie some major symptoms in stress-related mental disorders. This includes low reward salience as the basis for diminished interest or pleasure in major depressive disorder (MDD) and for apathy (negative symptoms) in schizophrenia, and high aversion salience as the basis for depressed mood in MDD. Insight into the brain region(s) and cellular microcircuits wherein the saliences of reward and aversion stimuli are set is essential for understanding the neurobiology of emotion in health and mental disorders. Here I review the current evidence for the role of the amygdala in processing reward valence and salience, based on studies conducted in human, monkey and, in particular, rat and mouse. Human BOLD-fMRI studies demonstrate amygdala reactivity to reward and its reduction in MDD and schizophrenia. In monkey, some neurons in the basolateral amygdala (BLA) are responsive to reward, aversion, or both. In rat, BLA reward neurons regulate excitation of nucleus accumbens (NAcc) neurons, whereas chronic stress increases intra-amygdala synaptic activity. In mouse, there are BLA glutamatergic principal reward neurons and aversion neurons. Based on this comparative evidence, this review concludes that the mammalian BLA reward neurons could constitute a major contributor to the neural circuitry of reward salience and a critical node in reward pathology.